2020
DOI: 10.1111/jfb.14307
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships of mesopelagic fishes from the equatorial and tropical Atlantic waters: influence of environment and body shape

Abstract: Length-weight relationships (LWRs) were estimated for 36 mesopelagic fish species collected from the equatorial and tropical Atlantic encompassing several oceanographic regions: oligotrophic, equatorial, Cape Blanc, Cape Verde and the Canary Islands. The sample was composed of myctophids (25 species), gonostomatids (5), sternoptychids (3), stomiids (2) and phosichthyids (1). The species were clustered according to body shape: "short-deep" (sternoptychids), "elongate" (gonostomatids, stomiids and some phosichth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 66 publications
(104 reference statements)
5
18
1
Order By: Relevance
“…Our study confirms the earlier observed influence of body shape on the parameters of LWRs in fishes in general and mesopelagic fishes in particular (Froese, 2006;L opez-Pérez et al, 2020) 3). Geographic regions are indicated by linetype, symbol and colour (EQ-C, dotted line, dark-blue square; EQ-N, two-dashed line, turquoise triangle; LO-E, solid line, red circle; LO-W, dashed line, violet diamond).…”
Section: Fishsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirms the earlier observed influence of body shape on the parameters of LWRs in fishes in general and mesopelagic fishes in particular (Froese, 2006;L opez-Pérez et al, 2020) 3). Geographic regions are indicated by linetype, symbol and colour (EQ-C, dotted line, dark-blue square; EQ-N, two-dashed line, turquoise triangle; LO-E, solid line, red circle; LO-W, dashed line, violet diamond).…”
Section: Fishsupporting
confidence: 92%
“…representative size ranges reported up to now (Battaglia et al, 2010;Eduardo et al, 2019Eduardo et al, , 2020aJiang et al, 2017;L opez-Pérez et al, 2020;Olivar et al, 2013;Sarmiento-Lezcano et al, 2018;Slayden, 2020;Wang et al, 2018). In 31 species, body lengths were within the maximum range of body lengths recorded in the area, with new records of maximum lengths for 13 species.…”
Section: Fishmentioning
confidence: 66%
See 1 more Smart Citation
“…For measurements of water weight and water content, 3 fish in each tank were sacrificed and dried for 1 h at 105°C and then weighted. Water weight (=weight before drying−weight after drying) and water content (=water weight/body weight × 100%) ( N = 9 for each group) were calculated thereafter (López‐Pérez et al, 2020). Eight fish were tail‐docked for blood sampling as described by Babaei et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…To define the size range of mesopelagic fish, we used the minimum and maximum recorded sizes from three datasets of mesopelagic fish length-weight measurements (85)(86)(87). The combined datasets contained samples from the trophic and equatorial Atlantic as well as the Southern Ocean and gave a body size range of 0.01-500gm for mesopelagic fish.…”
Section: Mesopelagicsmentioning
confidence: 99%